Feasibility, Accuracy, and Reproducibility of Aortic Valve Sizing for Transcatheter Aortic Valve Implantation Using Virtual Reality - Dominika Kanschik; Jafer Haschemi; Houtan Heidari; Kathrin Klein; Shazia Afzal; Oliver Maier; Kerstin Piayda; Stephan Binneboesssel; Goeksen Oezaslan; Raphael R. Bruno; Gerald Antoch; Artur Lichtenberg; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Detailed visualization and precise measurements of aortic valve dimensions are critical for the success of transcatheter aortic valve implantation and for the prevention of complications. Currently, multislice computed tomography is the gold standard for assessment of the aortic annulus and surrounding structures to determine the prosthesis size. New technologies such as virtual reality (VR) not only enable 3‐dimensional (3D) visualization with the potential to improve understanding of anatomy and pathology but also allow measurements in 3D. This study aims to investigate the feasibility, accuracy, and reproducibility of VR for the visualization of the aortic valve, the surrounding structures, and its role in preprocedural sizing for transcatheter aortic valve implantation. Methods and Results Based on the preprocedural multislice computed tomography data, 3mensio measurements and 3D visualizations and measurements using VR software were performed retrospectively on 60 consecutive patients who underwent transcatheter aortic valve implantation at our heart center. There were no significant differences but strong correlations between the VR measurements compared with those performed with the 3mensio software. Furthermore, excellent or good intra‐ and interobserver reliability could be demonstrated for all values. In a structured questionnaire, users reported that VR simplified anatomical understanding, improved 3D comprehension of adjacent structures, and was associated with very good self‐perceived depth perception. Conclusions The use of VR for preprocedural transcatheter aortic valve implantation sizing is feasible and has precise and reproducible measurements. In addition, 3D visualization improves anatomical understanding and orientation. To evaluate the potential benefits of 3D visualization for planning further cardiovascular interventions, research in this field is needed.